An in-vitro study to compare the temperature rise in the pulp chamber by direct method using three different provisional restorative materials - Ankita Piplani; M C Suresh Sajjan; A V Ramaraju; Tushar Tanwani; G Sushma; G Ganathipathi; K Jagdish; Anil Agrawal (Wolters Kluwer Medknow Publications, 2016)
Statement of Problem: The provisional restorative materials in fixed prosthodontics are basically bis-GMA resins which releases exothermic temperature while polymerization which can damage the pulp. Intrapulpal temperature exceeding 42.5°C found to result in irreversible damage to the pulp. The remaining thickness of dentine after tooth preparation control the conduction of heat released by the resins. Purpose:(1) To quantify the temperature changes in the pulp chamber using different provisional restorative materials. (2) To evaluate the peak temperature time of different materials used. (3) To compare the intrapulpal temperature changes with a variation in the width of the finish line. Methodology: Two intact mandibular molars were selected and designated as Specimen A and B. Tooth preparation was done to prepare a finish line of 1.2 mm and 1 mm width, respectively. Three provisional restorative materials were considered and they were grouped as Group I-Cool temp, Group II-Protemp-4, Group III-Integrity. A J thermocouple probe was placed into the pulp chamber to determine the rise in temperature. The temperature was recorded during polymerization at 30-s intervals until the peak temperature was reached. The same procedure was repeated for fabricating remaining provisional crowns. A total of 45 provisional crowns were fabricated for each specimen. Results: Kruskal-Wallis test revealed that there was a significant difference in the temperature changes associated with the provisional restorative materials used. All the three provisional restorative materials were compared for 1.2 mm and 1 mm wide finish line. Integrity produced the highest temperature rise and the maximum temperature recorded was 40.2°C in 1.2 mm wide finish line. However, for a 1 mm wide finish line, Protemp-4 produced the highest temperature rise and the maximum temperature recorded was 40.3°C. It was observed that peak temperatures with Specimen B were more when compared with Specimen A. Conclusion: Cool temp showed least temperature rise in the pulp chamber. The order of rise in intrapulpal temperature in tested provisional materials using direct technique would be Cool temp, Integrity, and Protemp-4.